Newly Isolated Paenibacillus monticola sp. nov., a Novel Plant Growth-Promoting Rhizobacteria Strain From High-Altitude Spruce Forests in the Qilian Mountains, China - Li, Hui-Ping; Gan, Ya-Nan; Yue, Li-Jun; Han, Qing-Qing; Chen, Jia; Liu, Qiong-Mei; Zhao, Qi; Zhang, Jin-Lin (Frontiers in Microbiology, 2022)
Species in the genus Paenibacillus from special habitats have attracted great attention due to their plant growth-promoting traits. A novel plant growth-promoting rhizobacteria (PGPR) species in the genus Paenibacillus was isolated from spruce forest at the height of 3150 m in the Qilian Mountains, Gansu province, China. The phylogenetic analysis based on 16S rRNA, rpoB and nifH gene sequences demonstrated that strain LC-T2T was affiliated in the genus Paenibacillus and exhibited the highest sequence similarity with Paenibacillus donghaensis KCTC 13049T (97.4%). Average nucleotide identity (ANIb and ANIm) and digital DNA-DNA hybridization (dDDH) between strain LC-T2T and Paenibacillus donghaensis KCTC 13049T were 72.6%, 83.3% and 21.2%, respectively, indicating their genetic differences at the species level. These differences were further verified by polar lipids profiles, major fatty acids contents and several distinct physiological characteristics. Meanwhile, the draft genome analysis provided insight into the genetic features to support its plant associated lifestyle and habitat adaptation. Subsequently, the effects of volatile organic compound (VOC) emitted from strain LC-T2T on the growth of Arabidopsis were evaluated. Application of strain LC-T2T significantly improved root surface area, root projection area and root fork numbers by 158.3%, 158.3% and 241.2%, respectively, compared to control. And the effects of LC-T2T on the growth of white clover (Trifolium repens L.) were further assessed by pot experiment. Application of LC-T2T also significantly improved the growth of white clover with root fresh weight increased over three folds compared to control. Furthermore, the viable bacterial genera of rhizosphere soil were detected in each treatment. The number of genera from LC-T2T-inoculated rhizosphere soil was 1.7 fold higher than that of control and some isolates were similar to strain LC-T2T, indicating that LC-T2T inoculation were effective in the rhizosphere soil of white clover. Overall, strain LC-T2T should be attributed to a novel PGPR species within the genus Paenibacillus based on phylogenetic relatedness, genotypic features, phenotypic and inoculation experiment, for which the name Paenibacillus monticola sp. nov is proposed.